2014
DOI: 10.4071/hitec-wp16
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Reliability Characterization of 1200 V Silicon Carbide Power MOSFETs and JFETs at High Temperatures

Abstract: 1200 V Silicon Carbide (SiC) Metal-Oxide-Semiconductor Field Effect Transistors (MOSFETs) and Junction Field Effect Transistors (JFETs) have been characterized at high operational temperatures. For packaged JFETs obtained from a collaborating manufacturer, the threshold shift (ΔVT) was measured under both static and dynamic voltage stress and, in all cases, was less than 2 mV, which is within the measurement margin of error. Temperatures up to 250°C and stress times as long as 200 hours were evaluated. As a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The well-known material, processing and cost issues associated with SiC devices has begun to subside, and with the development of 6" SiC substrates, this trend will continue. The SiC MOSFET is gaining acceptance, however the SiC MOS interface still suffers from reliability issues as compared to the SiC JFET [11]. For or this study, a normally-off 6.5 kV SiC JFET is compared to a super-cascode, where five normally-on 1.2 kV rated SiC JFETs are stacked serially with a low voltage Si-MOSFET to form a 6.0 kV rated switch exhibiting the desired normally-off behavior.…”
Section: Single Device Vs Super-cascode Discussionmentioning
confidence: 99%
“…The well-known material, processing and cost issues associated with SiC devices has begun to subside, and with the development of 6" SiC substrates, this trend will continue. The SiC MOSFET is gaining acceptance, however the SiC MOS interface still suffers from reliability issues as compared to the SiC JFET [11]. For or this study, a normally-off 6.5 kV SiC JFET is compared to a super-cascode, where five normally-on 1.2 kV rated SiC JFETs are stacked serially with a low voltage Si-MOSFET to form a 6.0 kV rated switch exhibiting the desired normally-off behavior.…”
Section: Single Device Vs Super-cascode Discussionmentioning
confidence: 99%
“…The experimental work in [1] has shown that, under both static and dynamic gate bias stress conditions, the SiC JFET devices have remarkably stable threshold voltages with a drift measured to be less than 10 millivolts at temperatures up to 250°C for 200 hours for packaged parts and 525°C for bare die. As a comparison, commercially available second-generation SiC MOSFETs demonstrate threshold voltage shifts of up to 300 millivolts after 30 minutes of static gate stress at 175°C.…”
Section: Introductionmentioning
confidence: 98%